The Role of the Consulate General of the Republic of Indonesia in Johor Bahru, Malaysia in Providing Services and Protection for Indonesian Citizens with Problems at Temporary Stopovers (TSS) (Literature Review of HR and Quality Management) - Muhammad Rusli (Dinasti International Journal of Education Management And Social Science, 2022)
Literature article Reviewing the Role of the Consulate General of the Republic of Indonesia Johor Bahru, Malaysia in Providing Services and Protection for Indonesian Citizens with Problems at Temporary Stopovers (TSS) is a scientific article that aims to build research hypotheses on the influence of variables that will be used in further research, within the scope of science. Human Resource Management and Quality Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) ; The service system affects the quality of service 2) the ability of employees affects the quality of service; 3) The service system has an effect on community satisfaction; 4) The ability of employees has an effect on Community Satisfaction; and 5) Service Quality has an effect on Community Satisfaction. Apart from these 2 exogenous variables that affect the endogenous variables of Service Quality and Community Satisfaction, there are still many other factors including the variables of Leadership, Attitude and Behavior, and Facilities.